Multiframe Target Localization With Strapdown Seeker Based on Self-Adaptive L-SHADE - Jiayang Wu; Huabo Yang; Hao Yang; Jiexin Zhou; Shifeng Zhang (International Journal of Aerospace Engineering)
Strapdown seekers are increasingly used in the terminal guidance for the advantages of small size and low cost. However, due to the coupling of the seeker with the missile and its limited field of view, there is a risk of losing the target. This paper proposes a multiframe fusion target localization method for missiles with strapdown seekers, which can still obtain the target location through the recorded state data even when the target is lost. First, some preprocessing approaches are applied to ensure the accuracy of target location estimation with the linear success history–based adaptive differential evolution (L-SHADE) algorithm. Second, L-SHADE is extended into the self-adaptive linear success history–based adaptive differential evolution (SL-SHADE) algorithm to speed up the calculation of the target location to be applied onboard for actual flight use. Third, the simulation verifies its efficiency and further investigates the effect of parameter settings on the algorithm performance.